Rethinking the scale up of Integrated Management of Childhood Illness. (30th July 2018) - Patel, Smruti; Zambruni, Jerome Pfaffmann; Palazuelos, Daniel; Legesse, Hailemariam; Ndiaye, Ndeye Fatou; Detjen, Anne; Aboubaker, Samira
Abstract : The global community must come together to rethink approaches and translate existing knowledge into action, say Smruti Patel and colleagues